Strengthening health information dissemination methods for fisherfolk in rural communities in Ghana - Addo, Eugene; Adjei, Emmanuel; Kankam, Philip Kwaku (Record and Library Journal, 2024)
Background of the study: Fisherfolk are often exposed to physical hazards, environmental changes, economic fluctuations, and policy/regulatory changes while contributing to food security and economic development. Purpose: The study aimed to explore challenges in and ways to strengthen health information dissemination methods for fisherfolk in rural Ghana. Method: This study utilised a case study design with 26 participants from three rural fishing communities in Ghana's Keta Municipal District. Qualitative data was collected through interviews with five public health workers as well as focus group discussions with 21 fisherfolk. The study employed purposive and convenience sampling methods for the selection of participants. Data collected from the participants were analysed through the use of thematic analysis. Findings: The study revealed that fisherfolk depended on interpersonal and media sources to meet their multidimensional health information needs. Public health officials also leveraged interpersonal approaches to disseminate information to these communities. However, the fisherfolks encountered infrastructural and other barriers that hindered their ability to obtain health information. Conclusion: The study highlights the need to tailor health information dissemination approaches to the needs and preferences of fishing communities while strengthening the rural information infrastructure by the Ghana Health Service to more effectively disseminate and expand access to health information in these settings.